First record of Nematherium (Xenarthra, Mylodontidae) from the Pinturas Formation (Burdigalian, early Miocene), Santa Cruz Province, Argentina. (December 2019) - Brandoni, Diego; Novo, Nelson M.; Tarquini, Juliana; Tejedor, Marcelo F.
Abstract: The Pinturas Formation (Burdigalian, early Miocene) crops out at several localities in the upper valley of the Pinturas river and its tributaries, northwestern Santa Cruz Province, Argentina. It is divided into three sequences (lower, middle, and upper) and the recorded fauna mainly consists of mammals, especially rodents, native ungulates, primates, and xenarthrans (cingulates and ground sloths). A primitive member of the Mylodontidae (Xenarthra, Folivora), Nematherium was described by Ameghino and includes the multiple described species such as N. angulatum, and N. birdi . The aim of this contribution is to present the first record of Nematherium recovered from different localities within the middle sequence of the Pinturas Formation. The morphology and size of the specimens herein presented are similar to that of Nematherium . In the skull, the tooth row diverges anteriorly and the palate is flat ahead of M3 and markedly convex behind the M3; the shape of the m1–m3 is similar to that of other species; although differences are related to the shape of the m4. The similarities and differences allow referring specimens from the Pinturas Formation to Nematherium sp. In addition to the record from the Pinturas Formation, Nematherium was recorded during the Burdigalian Stage/Age (early Miocene) at several localities of the Santa Cruz Formation, the upper levels of Sarmiento Formation (Argentina), and from the Cura-Mallín and Palomares formations (Chile). Nematherium is a guide fossil for the Burdigalian Stage/Age of the south of South America. Graphical abstract: Image 1 Highlights: The first record of Nematherium from the Pinturas Formation is presented. Nematherium was recorded during the Burdigalian Stage/Age (early Miocene). Nematherium was recorded from localities of Argentina and Chile. Nematherium is a guide fossil for the Burdigalian of the south of South America.